Metagenomic analyses of a microbial assemblage in a subglacial lake beneath the Vatnajökull ice cap, Iceland - Vannier, Pauline; Farrant, Gregory K.; Klonowski, Alexandra; Gaidos, Eric; Thorsteinsson, Thorsteinn; Marteinsson, Viggó þór (Frontiers in Microbiology, 2023)
Skaftárkatlar are two subglacial lakes located beneath the Vatnajökull ice cap in Iceland associated with geothermal and volcanic activity. Previous studies of these lakes with ribosomal gene (16S rDNA) tag sequencing revealed a limited diversity of bacteria adapted to cold, dark, and nutrient-poor waters. In this study, we present analyses of metagenomes from the lake which give new insights into its microbial ecology. Analyses of the 16S rDNA genes in the metagenomes confirmed the existence of a low-diversity core microbial assemblage in the lake and insights into the potential metabolisms of the dominant members. Seven taxonomic genera, Sulfuricurvum, Sulfurosprillum, Acetobacterium, Pelobacter/Geobacter, Saccharibacteria, Caldisericum, and an unclassified member of Prolixibacteraceae, comprised more than 98 % of the rDNA reads in the library. Functional characterization of the lake metagenomes revealed complete metabolic pathways for sulphur cycling, nitrogen metabolism, carbon fixation via the reverse Krebs cycle, and acetogenesis. These results show that chemolithoautotrophy constitutes the main metabolism in this subglacial ecosystem. This assemblage and its metabolisms are not reflected in enrichment cultures, demonstrating the importance of in-situ investigations of this environment.